Risks in Road Transportation of Sport Horses: the Case of Turkey - Elnaz Taghizadeh Alamdari; Bengü Sevil Oflaç; Aysu Göçer (Journal of Transportation and Logistics)
Horses are transported more frequently than any other animals (European Commission, 2002), but lack of education and knowledge in and control over their transportation leads to consequences harmful for the development and expansion of the industry. This study investigates the risks of horse transportation and aims to improve risk mitigation by proposing procedures and control systems. This study focuses particularly on racehorses and showjumping horses, considering their volume and the value of the equestrian market. Employing multi-method research, we aim to investigate the risks involved in horse transportation in Turkey and contribute to the related literature by creating a holistic approach with multiple parties involved in the industry. Semi-structured interviews were conducted with coaches, riders, grooms, drivers, a veterinarian, and a company owner in three cities of Turkey. The data revealed seven risk categories in horse road transportation: employee expertise, insurance issuance, horse health and safety, industry qualification, infrastructure, transportation planning, and vehicle design.